Pengaruh Pendidikan Konsumen dan Tingkat Pendapatan Orang Tua Terhadap Perilaku Konsumsi Mahasiswa Program Studi Pendidikan Ekonomi FKIP UNS - Sela Vitria Susilowati (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aims of this research are (1) to know a significant difference in student consumption behavior based on consumer education; (2) to know a significant difference in student consumption behavior based on parent's income level; (3) to know significant differences in student consumption behavior based on consumer education and income level of parents.The population in this research are students of Economic Education class of 2014-2017 which amounted 276 students. Sampling technique used in this research was proportional random sampling, so that there are 74 students selected to be samples. This research used quantitative method with comparative research. Data collected by questionnaire for consumer education and consumption behavior, while for income level data of parents collected by documentation. Analysis data technique used was two way anova.The results of this research are: (1) there is a significant differences in student consumption behavior based on consumer education. This is indicated by the value of F count 3.874> F Table with (p <0.05). (2), there is a significant difference in student consumption behavior based on the income level of the parents. This is indicated by the value of F count 5,315> F Table with (p <0.05). (3), there is a significant difference in student consumption behavior based on consumer education and income levels of parents. This is indicated by the value of F count 3.247> F Table with (p <0.05).